Interaksi Simbolik Kelompok Kebapakan (Studi pada Grup Facebook “Menjadi Bapak-Bapak: Bagian Pengantar - Revisi 2”) - Yasa, Kadek Sutama; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2021)
“Menjadi Bapak-Bapak: Bagian Pengantar – Revisi 2” is a group on Facebook that accomodates their members to interact each others like how a dad interact. This study purposes is to know and explain how the symbolic interactionism within the group’s member. This study is a descriptive-qualitative study which used Symbolic Interactionism theory by George Herbert Mead with its three main concept: ‘mind’, ‘self’ and ‘society’. The data in this study were collected using interview and documentation method. The study results show that the groups were founded to facilitate the members to can interact with “dad’s joke”, which is also being the symbols on this group. In ‘mind’ concept, the group members interprets dad’s jokes using cringe and unique typing style. In ‘self’ concepts, the group members build their own self concept through group interaction. In ‘society’ concepts, this group as a social network constructed by its members through their interaction. Keywords : Symbolic Interactionism, Mind, Self, Society